Analysis of tribo-charging during powder spreading in selective laser sintering: Assessment of polyamide 12 powder ageing effects on charging behavior - Hesse, Nicolas; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lübbert, Christian; Roth, Stephan; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2019)
Powder flowability is key to achieving high process stability and part quality by application of smooth and dense layers in selective laser sintering (SLS). This study sheds light on the rarely investigated effect of tribo-electric charge build-up during powder delivery in the SLS process. This is achieved by a novel approach to quantify electrostatic potentials during doctor blading. The presented model setup is used in combination with charge spectrometry and impedance spectroscopy to investigate the alterations in tribo-electric charging behavior for the most commonly used laser sintering material polyamide 12 in its virgin and aged, c.f. reused, states. We show that the electrostatic charge build-up is significantly enhanced for aged polymer powder material, likely contributing to altered performance in SLS processing.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Additive manufacturing; Charge distribution; Electrostatics; Polyamide 12; Polymer ageing; Powder layer formation; Selective laser sintering; Surface potential; Tribo-charging

A novel, precipitated polybutylene terephthalate feedstock material for powder bed fusion of polymers (PBF): Material development and initial PBF processability - Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Grünewald, Moritz; Popp, Kevin; Rudloff, Johannes; Lang, Marieluise; Schmidt, Jochen (Materials & Design, 2021)
The development of a novel polybutylene terephthalate (PBT) feedstock material for powder bed fusion of polymers with laser beam (PBF-LB/P) by means of liquid-liquid phase separation (LLPS) and precipitation is outlined. Appropriate solvents for precipitation have been identified by a screening approach based on solubility parameters. Feasible system compositions, and solution and cloud point temperatures were determined. For the most promising solvent cyclopentanone, a parameter study on the influence of stirring conditions during precipitation was performed. The obtained products were characterized with respect to their particle size distribution, particle shape, phase morphology, thermal properties and melt viscosity. Under optimized process conditions, PBT particles of high degree of crystallinity with narrow size distribution and a mean diameter of 36 μm were obtained; flowability was improved by dry coating. The initial PBF-LB/P processability was assessed by building single layers in a parameter study using a Formiga P110 machine. Dense single layers were obtained at laser power PL = 11.5 W, scanning speed vS = 4000 mm/s, hatch distance hS = 0.24 mm and layer thickness dS = 0.1 mm. Best to the authors' knowledge, this is the first study in the open literature reporting on a PBT feedstock material obtained by liquid-liquid phase separation and crystallizatio
Keywords: Polybutylene terephthalate (PBT); Powder bed fusion (PBF); Liquid-liquid phase separation (LLPS); Powder characterization; Spreadability; Processability

Characterization of Polymer Powders for Selective Laser Sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Hesse, Nicolas; Bück, Andreas; Peukert, Wolfgang (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Development of poly(L-lactide) (PLLA) microspheres precipitated from triacetin for application in powder bed fusion of polymers - Dechet, Maximilian; Demina, Anna; Römling, Lea; Gomez Bonilla, Juan Sebastian; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2020)
In this work, the development and processing behavior of poly(L-lactide) (PLLA) particles for powder bed fusion (PBF) of polymers obtained via a green and sustainable process route are thoroughly studied. Liquid-liquid phase separation and precipitation from triacetin, a non-toxic solvent, are applied for the production of highly spherical PLLA particles of excellent flowability. Starting from the measured cloud-point diagram of the PLLA-triacetin system, appropriate temperature profiles for the precipitation process are derived. The effect of process parameters on the product properties is addressed in detail; the PLLA particles are characterized regarding their size distribution and morphology. Furthermore, material properties including thermal behavior (c.f. processing window for powder bed fusion (PBF)) and powder flowability are assessed. The spherical PLLA particles of narrow size distribution display a wide sintering window of 59 K and an excellent flowability due to the intrinsic surface roughness of the particles. Thus, tensile test bars and complex porous gyroid specimens were successfully manufactured via PBF without the need for any additional surface functionalization of the particles with flow agents. The high potential of the newly developed PLLA powders produced via an environmentally friendly approach omitting the use of halogenated or toxic solvents, as well as flowing aids, is demonstrated by mechanical testing of the printed specimen

Effect of particle rounding on the processability of polypropylene powder and the mechanical properties of selective laser sintering produced parts - Gomez Bonilla, Juan Sebastian; Kletcher, Robin; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
Common techniques for the production of polymer powders for selective laser sintering (SLS) involve the comminution of polymers. Comminution of polymers often results in powders made of irregular shaped particles with a low bulk density and a bad flow behavior. With the aim to improve the flowability of grinded powders and, thus, the SLS processability, a thermal process for particle shape modification was developed. This has been applied successfully for a broad variety of thermoplasts. In this contribution, a modified design of a rounding reactor with direct heating and optimized geometry is presented. The performance of the new design is assessed by the rounding of commercially available polypropylene powders. The influence of the rounding process on the packing density, flowability and particle size and shape distributions of the powders is investigated. Test specimens produced by SLS were tested to assess the effect of the rounding process on the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Comminution; Compressive strength; Laser heating; Particle size; Polypropylenes; Powders; Sintering; Modified designs; Optimized geometries; Packing density; Particle size and shape; Polymer powders; Selective laser sintering (SLS); Shaped particles; Thermal process

Improvement of polymer properties for powder bed fusion by combining in situ PECVD nanoparticle synthesis and dry coating - Gomez Bonilla, Juan Sebastian; Düsenberg, Björn; Lanyi, Franz; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Plasma Processes and Polymers, 2021)
Polypropylene (PP) powders are coated with silica nanoparticles in a fluidized bed to improve the flow behavior of the powders and the processability in powder bed fusion. The nanoparticles are produced in situ via dusty plasma‐enhanced chemical vapor deposition (PECVD) in an atmospheric‐pressure Ar/O2 plasma jet fixed at the distributor plate of the fluidized bed. Hexamethyldisiloxane is used as a precursor of the nanoparticles. The influence of the oxygen concentration in the plasma gas and the number of treatment cycles on the chemical composition of the nanoparticles, the amount of nanoparticles deposited, and the flow properties of the coated PP powders is investigated. The chemical composition of the formed silica particles is determined by X‐ray photon spectroscopy and infrared spectroscopy. The results reveal that the composition of the nanoparticles is SiOxCy, that is, the portion of organic residues introduced by the precursor can be controlled by changing the oxygen concentration in the plasma gas. The mass of nanoparticles deposited on the polymer powder's surface, as determined by inductively coupled optical emission spectroscopy, shows a linear dependence of the number of cycles and the oxygen concentration in the plasma gas. A considerable improvement of the flow behavior of the PP powders is observed after PECVD treatment.<br
Keywords: nanocomposites; particle coating; plasma‐enhanced chemical vapor deposition; powder bed fusion; powder flowability

Improving the coloring of polypropylene materials for powder bed fusion by plasma surface functionalization - Gomez Bonilla, Juan Sebastian; Szymczak, Tim; Zhou, Xuemei; Schrüfer, Stefan; Dechet, Maximilian; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Additive Manufacturing, 2020)
Polypropylene (PP) powder is treated in a fluidized bed reactor with an atmospheric Ar/O2 plasma jet to investigate the influence of the plasma treatment on the coloring of the powders. The oxygen concentration in the plasma gas and duration of the treatment was varied. Contact angle and X-ray photoelectron spectroscopy measurements confirmed and quantified the formation of surface functionalities and their dependence on the process parameters. The plasma treatment contributes to a significant improvement of the dispersibility and coloring of PP. Powder bulk properties such as particle size distribution and flowability were not modified by the process. Effects of the plasma treatment on the material bulk properties are also negligible.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Color strength; Dispersibility; Plasma surface functionalization; Powder bed fusion; Powder coloring; Wettability

Non-invasive investigation of the cross-sectional solids distribution in CFB risers by X-ray computed tomography - Hensler, Timo; Firsching, Markus; Gomez Bonilla, Juan Sebastian; Woerlein, Thorsten; Uhlmann, Norman; Wirth, Karl-Ernst (Powder Technology, 2016)
We apply X-ray computed tomography for non-invasive investigation of the distribution of solids over the cross-section of a pilot plant scale circulating fluidized bed riser and present a novel method to derive volumetric solids concentrations from tomographic raw data. In this, the elimination of low-energetic radiation from the incident X-ray spectrum plays an essential role to avoid detrimental beam hardening effects, which are caused by the pipe material and the fluidized solids. The presented technique is applied for quantitative analysis of the radial solids concentration distribution in a gas-solid circulating fluidized bed riser. The examined operating range covers mean solids concentrations between 2.7 vol% and 37.2 vol% whilst the superficial gas velocity is varied between 1.5 m s-1 and 6.0 m s-1. The high spatial resolution of the measured data permits evaluation of the influence of the overall solids holdup and the superficial gas velocity on the radial solids concentration profile. Comparison of the cross-section averaged solids concentrations obtained by X-ray computed tomography with those inferred from differential pressure measurements confirms the high accuracy of the applied method. Based on a comprehensive set of measurement data a model is developed that allows for the prediction of the radial solids concentration distribution in vertical gas-solid upflow.
EAM Import::2019-03-08

Novel process routes towards the production of spherical polymer powders for selective laser sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Kloos, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (AIP Conference Proceedings, 2019)
Additive manufacturing processes allow the production of individualized and complex parts without the use of molds or tools. Especially powder and beam-based AM processes like selective laser sintering (SLS) of polymers are promising, although the choice of commercial SLS powders is very limited. To further extend the applications of SLS, new and cheap materials with good processability must be supplied. Within this contribution two innovative methods for production of spherical polymer micro particles for SLS are discussed: The first approach is a process chain applicable to a wide range of polymers consisting of wet grinding in a stirred media mill followed by rounding of the obtained irregularshaped particles in a heated downer reactor and subsequent dry coating of the spherical particles for improvement of powder flowability. It will be outlined for glass-filled PBT systems. The second approach is melt emulsification with subsequent dry coating. In this process a polymer melt is emulsified by elongational and shear stresses in a rotor stator device. The method is exemplified for polypropylene (PP). Both approaches allow for production of spherical polymer micro particles. The effect of flowability, shape and bulk density on the powders' processabilities in SLS is assessed.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Melt emulsification; Polymer powder; Rounding

Particle Residence Time Distribution in a Concurrent Multiphase Flow Reactor: Experiments and Euler-Lagrange Simulations - Unger, Laura; Gomez Bonilla, Juan Sebastian; Dos Santos, Dyrney Araujo; Bück, Andreas (Processes, 2022)
The present work focuses on investigating the residence time behavior of microparticles in a concurrent downer reactor through experiments and numerical simulations. For the numerical simulations, a three-dimensional multiphase model was developed using the Euler-Lagrange approach. The experiments were performed in a 0.8 m-long steel reactor with gravitational particle injection. The effects of different operating conditions, e.g., the sheath gas velocity on the particle residence time distribution were assessed. An increase in the sheath gas flow rate led to a decrease in the peak residence time, although the maximum residence time increased. Regarding the lowest sheath gas flow rate, the particles' peak residence time was twice as high compared to the peak residence time within the highest flow rate. The particles' residence time curves presented a broad distribution coinciding with the size distribution of the powder. The numerical results agreed with the experimental data; thus, this study presents a numerical model for predicting the particle residence time behavior in a concurrent downer reactor. Furthermore, the numerical simulations contributed to a better understanding of the particle residence time behavior inside a concurrent downer reactor which is essential for optimizing thermal rounding processes. Dimensionless correlations for the observed effects are developed.
CRIS-Team WoS Importer:2022-06-17
Keywords: residence time distribution; axial flow structure; downer reactor; gas-particle flow; thermal rounding

Process Routes towards Novel Polybutylene Terephthalate – Polycarbonate Blend Powders for Selective Laser Sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Bück, Andreas; Peukert, Wolfgang (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Production of polybutylene terephtalate glass composite powders and characterization for processing in selective laser sintering - Schmidt, Jochen; Gomez Bonilla, Juan Sebastian; Sachs, Marius; Lanzl, Lydia; Wudy, Katrin; Wirth, Karl-Ernst; Drummer, Dietmar; Peukert, Wolfgang (26th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference, 2016)

Spherical Polybutylene Terephtalate (PBT)-Polycarbonate (PC) Blend Particles by Mechanical Alloying and Thermal Rounding - Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lanzl, Lydia; Drummer, Dietmar; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2018)
In this study, the feasibility of co-grinding and the subsequent thermal rounding to produce spherical polymer blend particles for selective laser sintering (SLS) is demonstrated for polybutylene terephthalate (PBT) and polycarbonate (PC). The polymers are jointly comminuted in a planetary ball mill, and the obtained product particles are rounded in a heated downer reactor. The size distribution of PBT-PC composite particles is characterized with laser diffraction particle sizing, while the shape and morphology are investigated via scanning electron microscopy (SEM). A thorough investigation and characterization of the polymer intermixing in single particles is achieved via staining techniques and Raman microscopy. Furthermore, polarized light microscopy on thin film cuts enables the visualization of polymer mixing inside the particles. Trans-esterification between PBT and PC during the process steps is investigated via vibrational spectroscopy and differential scanning calorimetry (DSC). In this way, a new process route for the production of novel polymer blend particle systems for SLS is developed and carefully analyzed.
Keywords: polybutylene terephthalate (PBT); polycarbonate (PC); polymer blend particles; spheroidization; additive manufacturing; Raman microscopy; SEM staining; trans-esterification

Tailored modification of flow behavior and processability of polypropylene powders in SLS by fluidized bed coating with in-situ plasma produced silica nanoparticles - Gomez Bonilla, Juan Sebastian; Trzenschiok, Holger; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
The processability of selective laser sintering (SLS) powders and the characteristics of the generated parts depend amongst others on the flowability. To increase the flowability, SLS powders are usually functionalized with flowing agents. Flowing agents are typically applied by dry particle coating. The optimization of the process parameters necessary to achieve a homogenous coating avoiding segregation is still empirical. In this contribution, an alternative process to particle dry coating is presented. This process integrates the synthesis of silica nanoparticles via plasma enhanced chemical vapor deposition (PECVD) and coating of polymer host particles in a fluidized bed in a single process. The influence of the treatment time on the packing density and flow behavior of the powders is investigated. Test specimen are produced to assess the influence of the treatment on the processability of the powders and the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Coatings; Compressive strength; Fluidized bed process; Laser heating; Nanoparticles; Plasma CVD; Plasma enhanced chemical vapor deposition; Polypropylenes; Powders; Selective laser sintering; Silica; Silica nanoparticles; Sintering; Synthesis (chemical); Alternative process; Dry-particle coating; Fluidized bed coating; Homogenous coatings; Packing density; Process parameters; Selective laser sintering (SLS); Fluidized beds

Thermal rounding of micron-sized polymer particles in a downer reactor: direct vs indirect heating - Gomez Bonilla, Juan Sebastian; Dechet, Maximilian; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Rapid Prototyping Journal, 2020)
Purpose: The purpose of this paper is to investigate the effect of different heating approaches during thermal rounding of polymer powders on powder bulk properties such as particle size, shape and flowability, as well as on the yield of process. Design/methodology/approach: This study focuses on the rounding of commercial high-density polyethylene polymer particles in two different downer reactor designs using heated walls (indirect heating) and preheated carrier gas (direct heating). Powder bulk properties of the product obtained from both designs are characterized and compared. Findings: Particle rounding with direct heating leads to a considerable increase in process yield and a reduction in powder agglomeration compared to the design with indirect heating. This subsequently leads to higher powder flowability. In terms of shape, indirect heating yields not only particles with higher sphericity but also entails substantial agglomeration of the rounded particles. Originality/value: Shape modification via thermal rounding is the decisive step for the success of a top-down process chain for selective laser sintering powders with excellent flowability, starting with polymer particles from comminution. This report provides new information on the influence of the heating mode (direct/indirect) on the performance of the rounding process and particle properties.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Crystallinity; Particle shape; Particle size; Polymers; Powder flowability; Selective laser sintering; Shape modification; Thermal rounding